AKTUALISASI ASAS OTONOMI DALAM UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG OTONOMI DAERAH - Hera Fauziah; Mexsasai Indra; Abdul Ghafur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Regional autonomy in Indonesia have set up a republic constitution in 1945 after the amandements stipulated in article 18 republic constitution 1945. Autonomy regulate the principle of decentralization, deconcentration and assistance. One such principle is decentralization. In development since Indonesia’s independence to reform implementation. The principle of decentalization in legislation to increase local autonomy towards regional autonomy in accordance with the constitutional mandate, but from the juridical aspect, namely the law number 23 of 2014. Has not been able to pt the principle of decentralization as a cornerstone in the implementation of regional autonomy, the actualization of law number 23 of 2014 leading to a centralized regional autonomy. Causing imbalance affairs division of authority between the center and regions. Based on this understanding the writing of this formulated two formulation of the problem. First, how is the actualization of the principle of local autonomy in the law number 23 of 2014, the second whether laar behind changes in the law number 23 of 2014.The kind of research is legal normative and descriptive analysis. Data sources supported by the data source of primary, secondary and tertiary data. Data collection techniques used is the study of literature. After data is collected than analyzed qualitatively, then concludes with a deductive method of thinking to analyze the problems of the general form into special shapes.O the research problem, there are two main things that can be cocluded, first, the principle of local autonomy principle enshrined in the law of local government has not been able performing well. This is because some of the content of article 23 of 2014 the changes are not consistent with the spirit of regional autonomy development, second, some of the provisions of clauses in the legislation led to a shift of power centers that make desentralization to authoritarian.Keywords : actualization – the principle of local autonomy